Viabilidade da implantação e operação de um biodigestor modelo bombona para o aproveitamento de dejetos bovinos em propriedades rurais no entorno do lago de Tucuruí - SOUZA, Dacio Janio da Costa (2023)
In the state of Pará, livestock is consolidated as one of the main economic activities, with a herd of approximately 26,754,388 heads of cattle in 2023. The seven municipalities around Lake Tucuruí/PA are responsible for approximately 2,758,700 animals. The volume of waste generated by these animals without proper disposal and treatment, causes impacts on the environment. The use of biodigesters is a clean and viable treatment alternative in the generation of energy OR fuel, the use of organic matter as a power source makes the biodigester highly sustainable. This work was carried out in two different municipalities, one in the rural area of the municipality of Breu Branco/PA, the other in the urban area of the municipality of Tucuruí/PA, with the aim of proposing solutions and improvements to small producers, and analyzing the implementation and operation of a bombona model biodigester using bovine manure. The methodology applied was through a case study, then the place where the biodigester would be implanted in the properties was chosen, soon after the biodigester model to be used and the organic matter that would be used were chosen, finally it was done an operational and financial analysis of the system used. The biodigester cost R$ 424.10, an amount referring only to the materials used, labor costs are not included, as it is a simple and easy-to-use piece of equipment, any producer with the proper instructions can assemble his own biodigester. It was concluded that the use of biodigestors in rural properties is a viable alternative from an economic and environmental point of view.